Coding of "Home Cage" by PFC Neurons. (21st November 2018) - Yan, Rongzhen; Zhou, Qiang
Highlights: Ventral medial PFC neurons showed increase (ON) and decrease (OFF) in spike rates when mice entering or leaving home cage. Changes in spike rates were not affected by novelty or emotional significance of environmental contexts. Differences in basal spike rates of ON and OFF unit allow encoding of home cage. Abstract: Contexts play critical roles in many important aspects of an animal's routine functions, such as the interpretation of incoming signals and retrieved memories. The roles played by prefrontal cortex (PFC) neurons in the coding of contexts have been largely studied in relation to aversive stimuli (such as foot shock in conditioned fear). Whether PFC neurons may code contexts that mice encounter in everyday life, such as their home cage, is poorly understood. Here, we report the identification of a subpopulation of ventral medial PFC (vmPFC) neurons which change their spike rates when mice enter or leave their home cages. Both increase (ON units) and decrease (OFF units) in spike rate were observed, with about 2/3 of neurons showing decrease and 1/3 showing increase. These changes were evident whenever transitions occur from home cage to a different environment regardless of the novelty of the environments. In addition, changes in firing rate were not affected when mice entering a context where fear conditioning had taken place after contextual or auditory/cued fear conditioning. Furthermore, we found that the differential spike rates of ON and OFF units appear to allow mice to recognize that they are inside their home cages. Together, vmPFC neural spiking appears to enable the encoding of "home cage".